2018
DOI: 10.1080/17435390.2018.1446560
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing analysis shows that titanium dioxide nanoparticles induce endoplasmic reticulum stress, which has a central role in mediating plasma glucose in mice

Abstract: Titanium dioxide nanoparticles (TiO NPs) constitute the top five NPs in use today. In this study, oral administration of 50, 100, and 200 mg/kg body weight (b.w.) TiO NPs increases plasma glucose in mice, whereas 10 and 20 mg/kg b.w. TiO NPs did not. RNA sequencing (RNA-seq) technology was used to investigate genome-wide effects of TiO NPs. Clustering analysis of the RNA-seq data showed the most significantly enriched gene ontology terms and KEGG pathways related to the endoplasmic reticulum (ER) and ER stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 33 publications
2
65
0
1
Order By: Relevance
“…Based on previous studies, we designed an experiment to examine TiO 2 NP‐induced ER stress and ROS generation . Our results showed that GRP78 and CHOP mRNA and protein expression, mRNA and protein ratios of XBP1‐s/t, and protein ratio of ATF6 (90/50 kD) were significantly increased from week 5, indicating that ER stress is induced at this time.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Based on previous studies, we designed an experiment to examine TiO 2 NP‐induced ER stress and ROS generation . Our results showed that GRP78 and CHOP mRNA and protein expression, mRNA and protein ratios of XBP1‐s/t, and protein ratio of ATF6 (90/50 kD) were significantly increased from week 5, indicating that ER stress is induced at this time.…”
Section: Discussionmentioning
confidence: 87%
“…In earlier studies on mice treated with 0, 10, 20, 50, 100, and 200 mg/kg b.w. TiO 2 NPs, concentrations of 50, 100, and 200 mg/kg led to elevation of plasma glucose . At an adult intake of 0.36 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, Hu et al showed that TiO 2 NPs activated a monooxygenase system in mice, as an exogenous compound . Cytochrome P450s, such as Cyp2b9, Cyp2c70, and Cyp4a14, participate in xenobiotic biodegradation and play a primary role in the monooxygenase system .…”
Section: Discussionmentioning
confidence: 99%